Functional expression of HLA-DP genes transfected into mouse fibroblasts. - Austin, P; Trowsdale, J; Rudd, C; Bodmer, W; Feldmann, M; Lamb, J (1985)
The HLA class II antigens are a highly polymorphic family of dimeric cell-surface glycoproteins, expressed predominantly on the surface of immunocompetent cells. They are intimately involved with the induction of the T-cell response to extrinsic antigen and are important predisposing factors for a wide spectrum of autoimmune diseases. We describe here the expression of a class II product from the HLA-DP (new WHO nomenclature, formerly SB) subregion after transfer of cloned genes into mouse fibroblasts. The transfected DP antigen is recognized by several HLA class II monoclonal antibodies and, though present in a mouse cell background, is able to function in the presentation of influenza antigen to cloned DP-restricted human T lymphocytes.